Estimation of the Sea Level Rise by 2100 Resulting from Changes in the Surface Mass Balance of the Greenland Ice Sheet - Fettweis, Xavier; Belleflamme, Alexandre; Erpicum, Michel; Franco, Bruno; Nicolay, Samuel (IntechOpen, 2011)
None